Childhood to adulthood: Accounting for age dependence in healthy‐reference distributions in 129Xe gas‐exchange MRI. Issue 3 (13th November 2022) - Plummer, Joseph W.; Willmering, Matthew M.; Cleveland, Zackary I.; Towe, Christopher; Woods, Jason C.; Walkup, Laura L.
Abstract : Purpose: Xenon‐129 ( 129 Xe) gas‐exchange MRI is a pulmonary‐imaging technique that provides quantitative metrics for lung structure and function and is often compared to pulmonary‐function tests. Unlike such tests, it does not normalize to predictive values based on demographic variables such as age. Many sites have alluded to an age dependence in gas‐exchange metrics; however, a procedure for normalizing metrics has not yet been introduced. Theory: We model healthy reference values for 129 Xe gas‐exchange MRI against age using generalized additive models for location, scale, and shape (GAMLSS). GAMLSS takes signal data from an aggregated heathy‐reference cohort and fits a distribution with flexible median, variation, skewness, and kurtosis to predict age‐dependent centiles. This approach mirrors methods by the Global Lung Function Initiative for modeling pulmonary‐function test data and applies it to binning methods widely used by the 129 Xe MRI community to interpret and quantify gas‐exchange data. Methods: Ventilation, membrane‐uptake, red blood cell transfer, and red blood cell:membrane gas‐exchange metrics were collected on 30 healthy subjects over an age range of 5 to 68 years. A GAMLSS model was fit against age and compared against widely used linear and generalized‐linear binning 129 Xe MRI analysis schemes. Results: All 4 gas‐exchange metrics had significant skewness, and membrane‐uptake had significant kurtosis compared to a normal distribution. Age has significant impact on distribution parameters. GAMLSS‐binning produced narrower bins compared to the linear and generalized‐linear binning schemes and distributed signal data closer to a normal distribution. Conclusion: The proposed "proof‐of‐concept" GAMLSS‐binning approach can improve diagnostic accuracy of 129 Xe gas‐exchange MRI by providing a means of modeling voxel distribution data against age.